ANGGARAN BERBASIS KINERJA, SUMBER DAYA MANUSIA, DAN KUALITAS ANGGARAN SKPD (Suatu Pengujian Struktural) - Octariani, Devie; Akram, Akram; Animah, Animah (Riset Akuntansi dan Keuangan Indonesia, 2017)
The aims of this study are to examine and analyze the effect of implementation of performance based budgeting, and quality of human resources to regional work unitâs (SKPD) budget qualities. Goal setting theory and agency theory are used to explain the phenomenon of budget qualities. The number of respondents in this study were 94 respondents that selected using purposive sampling method, the criteria that SKPD which has been tested for compliance by the Ombudsman in 2015 related to quality of service. This research uses analytical techniques Partial Least Square (smartPLS) 3.0. The results of quantitative analysis in this study showed that implementation of performance based budgeting, and quality of human resources had influence on SKPDâs budget qualities. The implications of this study can be useful for SKPDs on local governments to implement the principles of good governance and performance-based budgeting in the budget process to be able to provide better services to the public.Keywords: Budgeting, Budget Qualities, Performance Based Budgeting, Quality of Human Resources.